SPD_0090 Negatively Contributes to Virulence of Streptococcus pneumoniae - Cao, Linlin; Li, Nan; Dong, Yingshan; Yang, Xiao-Yan; Liu, Jiajia; He, Qing-Yu; Ge, Ruiguang; Sun, Xuesong (Frontiers in Microbiology, 2022)
In most bacteria, iron plays an important role in the survival of bacteria and the process of infection to host. Streptococcus pneumoniae (S. pneumoniae) evolved three irons transporters (PiaABC, PiuABC, and PitABC) responsible for the transportation of three kinds of iron. Our previous study showed that both mRNA and protein level of SPD_0090 were significantly upregulated in the ΔpiuA/ΔpiaA/ΔpitA triple mutant, but its detailed biological function is unknown. In this study, we constructed spd_0090 knockout and complement strain and found that the deletion of spd_0090 hinders the bacterial growth. SPD_0090 is located on the cell surface and affects hemin uptake of S.pneumoniae. The cell infection model showed that the knockout strain had stronger invasion and adhesion ability. Notably, the knockout of spd_0090 gene resulted in an enhanced infection ability of S. pneumoniae to mice by increasing the expression of virulence factors. Further iTRAQ quantitative proteomics studies showed that the knockout of spd_0090 inhibited the carbon metabolism and thus suppressed bacterial growth. Our study showed that SPD_0090 negatively regulates the virulence of S. pneumoniae.